SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI PRAKTEK DOKTER BPJS DI KOTA LUBUKLINGGAU BERBASIS WEB MOBILE - joni karman (Jurnal Teknologi Informasi Mura, 2021)
The problem with this research is that in the city of lubuklinggau, there has not been a geographical information system for mapping the location of BPJS practices, so people are having a hard time finding out information about the location and location of the existing BPJS physician in the city of lubuklinggau. The study USES the methods of data collection, by applying direct observation and annotations to the research site (observations), by conducting immediate queries to the source (interviews), and by reading the literature manuals. Research shows that programs regarding geographic information systems mapping the location of BPJS practices in the city of lubuklinggau used PHP programming language and mysql databases. It can be concluded that the gographic information system for mapping the location of this web-based physician BPJS can enable people to more easily obtain information for mapping the range of BPJS's location in the city of lubuklinggau.